Indigofera linifolia ameliorated CCl4 induced endoplasmic reticulum stress in liver of rat. (1st March 2022) - Naz, Irum; Khan, Muhammad Rashid; Zai, Jawaid Ahmed; Batool, Riffat; Maryam, Sonia; Majid, Muhammad
Abstract: Ethnopharmacological relevance: Indigofera linifolia (L.f.) Retz. is used in subcontinent for liver disorders, in wounds, febrile eruption and as diuretic. Aim of study: The current study evaluates the protective effects of the methanol extract of Indigofera linifolia (ILM) on CCl4 -induced endoplasmic reticulum (ER) stress in liver of rat. Methods: ILM was analyzed for phytochemical classes, total phenolic (TPC) and flavonoid content (TFC) as well as multidimensional in vitro antioxidant assays. Male (Sprague Dawley) rats were dispersed into seven groups (6 rats/group) receiving 0.9% saline (1 ml/kg bw), CCl4 (1 ml/kg bw) diluted in olive oil (3:7 v/v), silymarin (200 mg/kg bw) + CCl4 (30% v/v), ILM (150 mg/kg bw) + CCl4 (30% v/v), ILM (300 mg/kg bw) + CCl4 and ILM alone (either 150 mg/kg bw or 300 mg/kg bw). Results: ILM extract was constituted of different phytochemical classes. Co-administration of ILM along with CCl4 to rat revert the level of alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP) and total bilirubin in blood serum and antioxidant parameters in liver. Further, CCl4 increased the level of ER stress markers and inflammatory mediators while decreased level of GCLC and Nrf-2 in liver tissues of rat. CCl4 -induced histopathological variations were reduced with ILM co-administration in liver tissues. Conclusion: The results suggest that active phyto-constituents of I. linifolia might be responsible for its antioxidant, anti-inflammatory and gene-regulating activities. Graphical abstract: Image 1